2022
DOI: 10.1002/adfm.202210765
|View full text |Cite
|
Sign up to set email alerts
|

Ruddlesden–Popper Perovskite Nanocrystals Stabilized in Mesoporous Silica with Efficient Carrier Dynamics for Flexible X‐Ray Scintillator

Abstract: The development of metal-halide perovskite nanocrystals (NCs) that yield bright and stable emission is of great importance. Previous reported perovskite NCs are mostly based on APbX 3 -type family fabricated via ligand-or surfactant-assisted chemical approaches. However, realizing bright and stable emission remains a challenge because of desorption of ligands/surfactants during long-term operation. Herein, Ruddlesden-Popper (RP)-type (A) 2 (MA) n-1 Pb n Br 3n+1 NCs with size less than Bohr radius stabilized in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 50 publications
2
16
0
Order By: Relevance
“…[21][22][23] The pre-synthesized perovskite microcrystals could be directly embedded within polymethyl methacrylate, polydimethylsiloxane (PDMS), or other polymers to realize flexible applications. [24][25][26][27][28] However, during the curing process of these polymers, there is an inevitable agglomeration of these crystals, which generally leads to a degraded performance of the as-obtained films. [23] Although in situ crystallization procedure is developed to form flexible perovskite composite films, [20,29,30] the Ostwald ripening and agglomeration of the perovskite nanocrystals still cannot be overlooked, which not only increases the light scattering of the corresponding scintillator film, but also limits the loading concentration of the perovskite nanocrystal scintillators, leading to low scintillation output.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] The pre-synthesized perovskite microcrystals could be directly embedded within polymethyl methacrylate, polydimethylsiloxane (PDMS), or other polymers to realize flexible applications. [24][25][26][27][28] However, during the curing process of these polymers, there is an inevitable agglomeration of these crystals, which generally leads to a degraded performance of the as-obtained films. [23] Although in situ crystallization procedure is developed to form flexible perovskite composite films, [20,29,30] the Ostwald ripening and agglomeration of the perovskite nanocrystals still cannot be overlooked, which not only increases the light scattering of the corresponding scintillator film, but also limits the loading concentration of the perovskite nanocrystal scintillators, leading to low scintillation output.…”
Section: Introductionmentioning
confidence: 99%
“…In the past couple of years, numerous strategies have been explored to enhance the stability of PQDs, such as the construction of inorganic low-dimensional perovskite nanocrystals, surface treatment with hydrophobic and strong electron-absorbing organic molecules, and using polymers or inorganic oxides to encapsulate PQDs. , Encapsulating PQDs with polymers or ceramic glass not only protects PQDs but also facilitates the creation of fluorescent films or glass for practical applications. Normally, PQDs are first prepared by hot injection or coprecipitation and then used for encapsulation, which involves cumbersome procedures .…”
Section: Introductionmentioning
confidence: 99%
“…This family of PNCs has been shown to form a natural multiple quantum well system, where efficient ultrafast energy funneling from small to large n layers (where n is the number of lead halide layered perovskite sheets in an inorganic layer) has been demonstrated in a mixed phase with an efficiency exceeding 85%. 98−101 One such work by Wang et al 102 reported a material design strategy and fabrication process to achieve RP-type (A) 2 (MA) n−1 Pb n Br 3n+1 PNCs within a mesoporous silica template (Figure 4b) exhibiting PLQYs > 99% and long-term stability under ambient or UV irradiation exposure.…”
mentioning
confidence: 99%